Lessons learned from a muscle study in nail-patella syndrome - Luisa Paul; Anne Schänzer; Christel Depienne; Andreas Hentschel; Nicolai Kohlschmidt; Ulrike Schara-Schmidt; Christopher Jannik Nelke; Andreas Roos; Heike Kölbel (Orphanet Journal of Rare Diseases)
Abstract Background Nail-patella (NPS) syndrome is an autosomal dominant disorder caused by mutations in the LMX1B gene and manifests with involvement of kidneys, nails, eyes as well as skeletal musculature. NPS shows some clinical similarities with Emery-Dreifuss muscular dystrophy. However, thus far human muscle tissue has not been analysed in the context of NPS to precisely clarify the muscular involvement in this multi-systemic disease. Methods To study the effects of a missense variant in LMX1B on human skeletal muscle, histological, immunofluorescence and ultra-structural studies were performed on a deltoid muscle biopsy performed at the age of 2 aiming to analyse potential pathologies in muscle fibres in addition to unbiased proteomic profiling to identify dysregulated proteins. Results Microscopic work-up of the muscle biopsy revealed no striking pathologies, except for some atrophic fibres. The proteomic analyses unveiled a clustered number of dysregulated keratin proteins among the downregulated proteins. Conclusion Although NPS can also present with a muscular phenotype indicated by muscular weakness of the upper extremities, elevated CK levels and contractures of the elbow joint, there is no evidence of primary muscular involvement due to expression of mutant LMX1B. The examination of human skeletal muscle tissue confirmed the findings from the animal models showing that the skeletal muscle symptoms of NPS may be the result of a developmental disorder of the extremities that leads to impaired muscle mobilisation.